Classical and celestial mechanics the Recife lectures - Cabral Hildeberto; Diacu Florin (Princeton Princeton Univ Press, 2002)
This book brings together a number of lectures given between 1993 and 1999 as part of a special series hosted by the Federal University of Pernambuco, in which internationally established researchers came to Recife, Brazil, to lecture on classical or cel
Keywords: Celestial mechanics; Many-body problem; Mechanics